What to do when good-quality embryos repeatedly fail to implant. (November 2018) - Coughlan, Carol
Abstract: Recurrent implantation failure (RIF) is very distressing for couples and frustrating for their clinicians who seek to find a solution.RIF is defined as the failure to achieve a clinical pregnancy following the transfer of at least four good-quality embryos in a minimum of three fresh or frozen cycles in a woman of age below 40 years. An agreed local protocol regarding how couples with RIF should be further investigated and managed should be in place. Ovarian function should be assessed by measuring antral follicle count, FSH, and AMH. Chromosomal testing of the couple is advised to exclude genetic abnormalities that may lead to RIF. Various uterine pathologies including fibroids, endometrial polyps, congenital anomalies, and intrauterine adhesions should be excluded by ultrasonography and hysteroscopy. Hydrosalpinges are a recognized cause of implantation failure and should be excluded by hysterosalpingogram, and if necessary, laparoscopy should be performed to confirm or refute the diagnosis. Consideration should be given to preimplantation genetic screening (PGS) and the adoption of a "freeze-all" protocol. Treatment offered should be evidence based, aimed at improving embryo quality or endometrial receptivity. Gamete donation or surrogacy may be necessary if there is no realistic chance of success with further IVF attempts.